A study on self-care practices and dietary barriers among type 2 diabetes patients attending outpatient department in Karnataka Institute of Medical Sciences, Hubballi - Kavya, N. P.; Bant, Dattatreya D. (International Journal Of Community Medicine And Public Health, 2019)
Background: Diabetes is a chronic, progressive disease characterized by elevated levels of blood glucose and is recognized as an important cause of premature mortality and morbidity. Self-care practice in diabetes patient is a critical factor to achieve glycaemic control thus in preventing or delaying its complications. Methods: A cross sectional study was conducted among 140 type 2 diabetic patients attending the outpatient department in Karnataka Institute of Medical Sciences, Hubballi during the period of June-July 2018. Diabetic patients diagnosed more than 3 months were included. Data was collected by interview method using pre-designed, pre-tested and semi-structured questionnaire which consists of information on socio-demographic data, diabetic profile, self-care practices and dietary barriers. Statistical analysis was done using SSPS package. Results: This study showed that 67.9% of study participants were consuming diabetic diet, 17.1% practice exercise for more than 3 days a week, 93.6% were taking medication regularly, 15% practised foot care for >3times a week and 89.3% monitored their blood glucose regularly. The main barriers for dietary practices were lack of knowledge (24%) and lack of motivation (18%). Compliance to diabetic diet was more among the urban population compared to rural (p=0.025). Conclusions: Study concludes that the practice of self-care activities was poor in almost all aspects except for blood sugar monitoring and adherence to medication which necessitates the need to create awareness regarding self-care practices and its importance among diabetic patients.